The medical profession and the medical college in two secular times: 1856-1956 - Pesce, Hugo (1956)
Keynote address delivered on September 20, 1956, in the action that the Peruvian Medical Federation featured in his clubhouse in honor of the Faculty of Medicine to commemorate the centenary of its founding.